Crystal structure of 2-(3-bromophenyl)-1,3-dithiane - Zukerman-Schpector, J.; Caracelli, I.; Stefani, H.A.; Gozhina, O.; Tiekink, E.R.T. (International Union of Crystallography, 2015)
In the title compound, C10H11BrS2, the 1,3-dithiane ring has a chair conformation with the 1,4-disposed C atoms being above and below the remaining four atoms. The bromobenzene ring occupies an equatorial position and forms a dihedral angle of 86.38 (12)° with the least-squares plane through the 1,3-dithiane ring. Thus, to a first approximation the molecule has mirror symmetry with the mirror containing the bromobenzene ring and the 1,4-disposed C atoms of the 1,3-dithiane ring. In the crystal, molecules associate via weak methylene-bromobenzene C - H⋯π and π-π [Cg⋯ Cg = 3.7770 (14) Å for centrosymmetrically related bromobenzene rings] interactions, forming supramolecular layers parallel to [101]; these stack with no specific intermolecular interactions between them.